Study of the effect of using of corticosteroids on the prognostic course of central nervous system infections - علي خلود; هالة سعيد; تغريد قدار (Latakia University Journal -Medical Sciences Series, 2022)
Background: Central nervous system(CNS) infections is considered as an important cause of morbidity and mortality worldwide in spite of a significant development in preventive measurements and management leading to poor outcome. Adjunctive steroid therapy was used to reduce inflammation in treatment of CNS infections across various causative pathogens. Aim: The purpose of this study was to determine the effects of using steroids on outcome in CNS infections. Materials and Methods: This was a Prospective Observational study involving 107 patients with a diagnosis of CNS infection with various types at Neurology unit, Internal Medicine Department, Tishreen University Hospital, Lattakia, during the period between April 2020-April 2021. Results: Out of 107 patients, 55 were male and 52 were female. Mean age of the patients was 51.20±9.8 without significant differences according to gender. Bacterial meningitis (48.6%) and herpes simplex virus meningitis (43.9%) represented the most frequent types of CNS infections. In bacterial meningitis, complete recovery was more frequent in patients receiving steroid (73.1% vs 57.7, p:0.06), whereas recovery with neurological complications and mortality were more frequent in patients who didn’t receive steroid (30.8% vs 19.2%, p:0.01) and (11.5% vs 7.7%, p:0.08) respectively. Complete recovery was more frequent in patients with herpes simplex virus meningitis who received steroid (88% vs 86.4%, p:0.1) and mortality was higher in patients who didn’t receive (9.1% vs 4%, p:0.08). In tuberculous meningitis, complete recovery was occurred in a patient who didn’t receive steroid, whereas complete recovery and recovery with neurological complications were occurred in 80% and 20% respectively in patients who receive steroid. In meningitis in HIV-infected patients, complete recovery developed in a patient who didn’t receive steroid with occurrence of mortality in a patient who did. Conclusion: Initiation of steroids in bacterial and viral CNS infections is considered a valuable method in improving the outcome.